GENRE ANALYSIS ON ENGLISH FRIDY SERMONS PREPARED BY THE ISLAMIC RELIGIOUS COUNCIL OF SINGAPORE - Liliek Soepriatmadji (Dinamika Bahasa dan Budaya, 2009)
A Friday Sermon delivery is a strategic mechanism for a Khatib (Preacher) to disseminate the divine truths—either from the quran, hadiths, Ijma’, or qiyas, and to convey the rights and responsibilities of Islam followers in respect to religious, social, economic and even political affairs. It is the language that plays a very significant role in encoding the Khatib’s messages. Therefore a Khatib (or any institution) preparing a sermon text needs to equip himself with a communication system in order to encode his social purposes. The system may prevent him from abusing the language to provoke the jama’ah (congregation). It may also lead him to use appropriate linguistic features to support the purposes, and to organize the purposes into a culturally recognized pattern or schematic structure to indicate that a sermon is different from other genres. To understand and describe the system we need to conduct a genre analysis on Friday Sermons using the model genre analysis offered by Eggins and Slade (1997). The English Friday sermons prepared by the Islamic Religious Council of Singapore were chosen and used as the model sermons to portray how purposes were encoded and organized into a particular generic structure potential.   Key Words: Communication system, Social/Communicative Purpose, Linguistic Features, Schematic Structure, Genre analysis, Generic Structure Potential